An application of the differential evolution optimization algorithm for solving raw material allocation problems in multi-echelon transportation. - Khuptawatin, Aekachai; Pitakaso, Rapeepan (Asia-Pacific Journal of Science and Technology, 2017)
The purpose of this compares the effects of algorithm for solving allocation problem in cassava transportation. Formulate the mathematical model analysis is computed by Lingo V.11 and Differential Evolution (DE) application. Two stages of conducting this research are 1) comparing stage, which compares the efficiency of the two employed applications according to accuracy economic, and 2) comparing stage, which compares the minimum computation time. The test to the proposed algorithm is tested with a simulation study to be in this research all five case studies. The results show that DE generates 0.281% worse than that of Lingo V.11 while using 85.4 minutes faster computational time than that of Lingo V.11.